Petani Ladang di Desa Winning Kecamatan Pasar Wajo Kabupaten Buton - Amrin, Ismawati Amrin; Janu, La; Rahman, Hidayah (JURNAL KABANTI: Kerabat Antropologi, 2025)
This research is entitled "Field Farmers in Winning Village, Pasar Wajo District, Buton Regency. This study uses the theory by Clifford Geertz (1983) regarding "from the Native's point of View" and the religious theory formulated by Preusz. The results of the study can be concluded that: The local knowledge possessed by farmers in Winning Village is by planting various types of crops in the fields, namely: rice (bhae), corn (kaitela), and vegetables (tawanakau). In farming these plants, each plant has its own local knowledge, the stages in farming are: (1) preparing land for farming. (2) rice plants, the stages are: planting rice using tugal with a distance between trees of about 15cm, rice plant care by making fences, harvesting rice using termites (pongkutu), and storing crops in kampiri. (3) corn plants, local knowledge, namely: planting corn using tugal with a distance between plants that is quite far about an adult's foot, protecting plants from pest attacks by making a fence around the field, harvested crops that are stored in a storage area (kampiri) above the attic of the house. (4) Vegetable crops, local knowledge possessed, namely: Vegetable plants chosen by farmers are types of vegetables that can be consumed by themselves and sold for sale. The belief system in farming is by carrying out rituals ranging from land preparation to storing crops that are addressed to the ancestors (ompu). (1) Rituals in rice farming, namely: khabelai and paburasa. (2) Rituals in corn farming, namely: khabelai, pengkaana-aana, katela mangura and pokambewe.